2023
DOI: 10.1002/lpor.202200841
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐Subwavelength Resonant Meta‐Optics Enabled by Ultra‐High Index Topological Insulators

Abstract: In nanophotonics, small mode volumes, high‐quality factor resonances, and large field enhancements without metals fundamentally scale with the refractive index and are key for many implementations involving light‐matter interactions. Topological insulators (TIs) are a class of insulating materials that host topologically protected surface states, some of which exhibit extraordinarily high permittivity values. Here, the optical properties of TI bismuth telluride (Bi2Te3) single crystals are studied. It is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…These results show that the NBs are ultracompact resonators with a dielectric-like response within cross-section sizes as small as ∼λ/8. The achieved confinement is comparable to other high-index chalcogenide Mie resonators such as Bi 2 Te 3 and PbTe, with respective unit cell sizes of ∼λ/11 and ∼λ/7, , and smaller than the reported confinements in polaritonic systems, such as hexagonal boron nitride (hBN) or SiC with unit cell sizes down to ∼λ/61. A finite-difference time-domain (FDTD) simulation (Details on FDTD simulations can be found in the Supporting Information), incorporating the extracted optical constants (Figure a) and the NB dimensions, is in good agreement with the experimentally obtained results (Figure c). Figure d shows the electric ( E , top) and magnetic ( H , bottom) field profiles of the fundamental resonant mode .…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…These results show that the NBs are ultracompact resonators with a dielectric-like response within cross-section sizes as small as ∼λ/8. The achieved confinement is comparable to other high-index chalcogenide Mie resonators such as Bi 2 Te 3 and PbTe, with respective unit cell sizes of ∼λ/11 and ∼λ/7, , and smaller than the reported confinements in polaritonic systems, such as hexagonal boron nitride (hBN) or SiC with unit cell sizes down to ∼λ/61. A finite-difference time-domain (FDTD) simulation (Details on FDTD simulations can be found in the Supporting Information), incorporating the extracted optical constants (Figure a) and the NB dimensions, is in good agreement with the experimentally obtained results (Figure c). Figure d shows the electric ( E , top) and magnetic ( H , bottom) field profiles of the fundamental resonant mode .…”
mentioning
confidence: 82%
“…Topological insulators (TIs) constitute a distinct category of materials characterized by a bulk energy gap (insulator-like), while also hosting time-reversal symmetry-protected gapless surface states. Fundamentally, TIs exhibit strong spin-orbit coupling, with the edge states allowing a flow of unidirectional supercurrent . These novel quantum states have been predicted theoretically as well as experimentally observed in several types of materials and systems such as CdTe/HgTe/CdTe quantum wells, strained HgTe, Sb 2 Te 3 /Sb 2 Te 3– y Se y , bismuth selenide (Bi 2 Se 3 ), , Bi 2 Te 3 , , Bi 2– x Sb x Te 3– y Se y , MnBi 2 Se 4 , ZrTe 5 , and more, with extensive research toward realizing novel electronic devices. , Recently, the unique properties of TIs have been explored in the context of electromagnetic and photonic systems. Among these, chalcogenide TIs are especially intriguing owing to their unique properties of low bulk bandgap, , exceptionally high values of permittivity, , and strong optical anisotropy . Recent studies have shown that these TIs are capable of generating high harmonics, , confining light in deep sub-wavelength structures, demonstrating unique plasmonic properties, , and hosting high-mobility surface states across a wide spectral range (visible to THz). ,, These findings highlight the vast potential of TIs in realizing novel devices with unparalleled properties. ,,,, …”
mentioning
confidence: 88%
See 3 more Smart Citations